2018
DOI: 10.1093/carcin/bgy141
|View full text |Cite
|
Sign up to set email alerts
|

Liver tumorigenesis is promoted by a high saturated fat diet specifically in male mice and is associated with hepatic expression of the proto-oncogene Agap2 and enrichment of the intestinal microbiome with Coprococcus

Abstract: Liver cancer results in a high degree of mortality, especially among men. As fatty liver disease is a risk factor for development of hepatocellular carcinoma, we investigated the role of dietary fat type in tumor promotion by high-fat diets in mice after initiation with the chemical carcinogen diethyl nitrosamine. Tumor incidence and multiplicity were significantly greater in males than those in females. In males, fat type had complex effects on tumorigenesis. Preneoplastic foci were most prevalent in mice fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
1
12
1
Order By: Relevance
“…The findings that are different here from previous studies are: 1) decrease in Bifidobacterium for all stages but less of a decrease seen for HCC, 2) the occurrence of another proinflammatory bacteria, Dorea which increases with stage of CLD (Leclercq et al, 2014), 3) the appearance of increased Coprococcus, a pro-inflammatory bacteria associated with western HFD which increases in CHB and LC but decreases in abundance in HCC (Pedersen et al, 2019), and 4) the decrease in Roseburia, an organism that cross-feeds other beneficial bacteria via it ability to degrade dietary β-mannans, with increasing disease stage (La Rosa et al, 2019).…”
Section: A Comparison Of Differential Bacterial Compositions Associatcontrasting
confidence: 99%
“…The findings that are different here from previous studies are: 1) decrease in Bifidobacterium for all stages but less of a decrease seen for HCC, 2) the occurrence of another proinflammatory bacteria, Dorea which increases with stage of CLD (Leclercq et al, 2014), 3) the appearance of increased Coprococcus, a pro-inflammatory bacteria associated with western HFD which increases in CHB and LC but decreases in abundance in HCC (Pedersen et al, 2019), and 4) the decrease in Roseburia, an organism that cross-feeds other beneficial bacteria via it ability to degrade dietary β-mannans, with increasing disease stage (La Rosa et al, 2019).…”
Section: A Comparison Of Differential Bacterial Compositions Associatcontrasting
confidence: 99%
“…In response to the HLA diet, we not only observed decreased abundance of Akkermansia but also of Sutterella, and increased abundance of Butyricimonas and Coprococcus. Alterations in the abundances of these bacteria in response to increased dietary lipid intake have been reported previously (3,26,32), indicating that all of these genera may be sensitive to the fatty acid content of the diet. Human pregnancy has previously been reported to reduce the individual (alpha) diversity of the gut microbiota in humans (21) and rodents (15).…”
Section: Discussionsupporting
confidence: 63%
“…Epidemiological studies have shown an association between NASH and HCC with an increased consumption of dietary fat, particularly saturated fats [19]. Saturated fatty acids (FAs) also stimulate release of the gastrointestinal (GI) peptide cholecystokinin (CCK), with a sharp cutoff in FA chain length [20,21].…”
Section: Introductionmentioning
confidence: 99%